Sustainable production and distribution practices in Atlantic Canadian short food supply chains: Explorative study - Balcom, Rebecca; Abebe, Gumataw Kifle; Yiridoe, Emmanuel K.; Hartt, Christopher M. (Frontiers in Sustainable Food Systems, 2023)
How food is produced, processed, distributed, and consumed significantly impacts the sustainability of food supply chains. Short food supply chains (SFSCs) have been promoted as an alternative approach to offer sustainable solutions. However, empirical studies provide mixed evidence, and the findings greatly vary based on context. This study explores the social, economic, and environmental sustainability practices from the perspective of farm businesses (producers) in Atlantic Canada’s SFSCs and the barriers thereof. A semi-structured study designed was employed. The findings show that most farm businesses linked to SFCSs have applied ecologically sound production methods such as organic farming, IPM, or other sustainable practices, including regenerative agriculture, and no-till farming. Over two-thirds of farm businesses applied sustainable practices such as predator insects and culture control to manage pests, pasture rotations, green fertilizers, low-carbon couriers, locally sourced inputs, compostable or recyclable packaging materials. Farm businesses in the Atlantic Provinces highly value social sustainability of SFSCs, followed by economic and environmental sustainability. Most farm businesses linked to SFSCs were robust to supply- and demand-side shocks, registered low number of layoffs, and fast recovery of operations and increased their profits during COVID-19 compared to pre-COVID-19 levels. Yet, several barriers remain, the most important ones being high capital costs and longer payback periods. Other barriers include inconsistent inter-provincial trading restrictions, lack of qualified workers and shrinking agricultural land base. In conclusion, SFSCs have shown promises by being resilient to supply- and demand-side shocks and socially, economically, and environmentally sustainable. This study expands our understanding of the characteristics of SFSCs in Atlantic Provinces. It provides insights into producers’ challenges to adopt sustainable practices in their production and distribution systems. However, SFSCs are unlikely to replace the more competitive longer food supply chains (LFSCs); therefore, policies supporting sustainability in the food system should promote the coexistence between SFSCs and LFSCs rather than as alternatives.